Tandem gas metal arc pipeline welding - Liratzis, Theocharis (Cranfield University, 2007)
Energy consumption has grown by 2% per year worldwide over the past ten years. In 2005 worldwide 900,000 barrels of oil and 7.6 billion cubic metre of natural gas were produced daily. The exploitation of fields to meet the increased demands in energy requires the presence of adequate infrastructures. High strength pipeline steels(X100) have been developed to operate at higher pressures allowing a greater volume of fuel to be transported. Additional advantages arising from the reduction in wall thickness contribute to reduction in construction costs and steel volume. Cont/d.